Professor Ts. Dr. Mohd Rusllim Mohamed appointed as President of AUSC - Mohd Aznorizamin, Ismail (2023)
KOTA SURABAYA, 7 December 2022 – Universiti Malaysia Pahang (UMP) continues to lead the Southeast Asian university sports arena when the Deputy Vice-Chancellor (Student Affairs & Alumni), Professor Ts. Dr. Mohd Rusllim Mohamed was appointed as the President of the Asean University Sports Council (AUSC) for the period 2023 to 2025 in the 5th AUSC General Assembly 2022 held at the Doubletree By Hilton Hotel in Kota Surabaya, East Java, Indonesia.